Peran Ibu Tunggal dalam Menjaga Kesehatan Mental Anak Usia Dini - Sri Wahyuni; Raden Diana (Generasi Emas, 2023)
The role of single mothers greatly influences children's mental health. The aim of this research is to find out the role of single mothers on children's mental health, the negative impact on children's mental health, and efforts to prevent mental health disorders in early childhood. The method used by this research is a case study which is presented as a qualitative descriptive research type with narrative data presentation, as well as data obtained through observation and interviews. In this study, the subject was a girl who experienced mental health problems aged 5-6 years due to the absence of a father figure in her life. The results of the research obtained are the role of single mothers who only provide physical needs without thinking about the psychological condition or mental health of the child. This gives rise to behavior that makes children become quiet, emotional, insecure, like to daydream due to lack of communication with the people around them. This mental health disorder in children requires serious efforts by single mothers or the adults around them, so that it does not have a negative impact on the child's development in the future.